BOOK REVIEWS (Journal of Finance, 1973)
Book reviewed in this article: Aggregate Theory and Policy; The New Inflation: Causes, Effects, Cures . By G. L. B ach . Aggregate Theory and Policy; The Theory of Macroeconomic Policy . By N ancy S. B arrett . Aggregate Theory and Policy; Some Cambridge Controversies in The Theory of Capital . By G. C. H arcourt . Aggregate Theory and Policy; Business Finance and Investments; Methodology in Finance—Investments . Edited by J ames L. B icksler Aggregate Theory and Policy; The Measurement of Portfolio Risk Exposure . By F rank B. C ampanella . Aggregate Theory and Policy; Modern Developments in Investment Management: A Book of Readings . Edited by J ames L orie and R ichard B realey Aggregate Theory and Policy; Theory of Financial Markets . By J an M ossin . Financial Institutions and Markets; Economics and Insurance: An Introduction to the Economic Aspects of Insurance By R. L. C arter . Financial Institutions and Markets; Inflation and Economic Development in Brazil 1946–1963 . By R aouf K ahil . Financial Institutions and Markets; Socialist Banking and Monetary Control: The Experience of Poland . By T. M. P odolski . International Finance; Super Imperialism: The Economic Strategy of American Empire . By M ichael H udson . Public Finance; The Payroll Tax for Social Security . By J ohn A. B rittain . Public Finance; Public Expenditure Analysis: Selected Readings . Edited by B albir S. S ahni .